New insights into superheated atomisation offer potential improvement in submicron particle size distribution for marine cloud brightening - Edmund Reardon; Adam Boies; Jake Chapman; Daniel Harrison; Dante McGrath; Hugh Hunt; Shaun Fitzgerald (Atmospheric Research, 2026)

Predicting amylose content, gelatinisation temperature, and RVA parameters of intact white rice using a portable NIR instrument - Joseph Robert Nastasi; Shanmugam Alagappan; Melissa A. Fitzgerald; Daniel Cozzolino (Journal of Cereal Science, 2026)

An L-moments-based hypothesis test to identify homogeneous storm transposition regions - Benjamin FitzGerald; Daniel Wright; Lei Yan; Alyssa Hendricks Dietrich; Antonia Sebastian (Journal of Hydrology, 2026)

Geographic distribution and notes on biology of Plecia plagiata (Wiedemann, 1824) (Diptera: Bibionidae) - Daniel de Castro Schelesky-Prado; Rafaela Lopes Falaschi; Scott J. Fitzgerald; Lívia Maria Fusari (Biologia, 2026)
Plecia plagiata (Wiedemann, 1824) is a species with a wide geographic distribution in the Neotropical region, with records in 20 countries. However, some records are notably vague, only mentioning the occurrence of the species in a certain country or region without a precise locality. This species had records for almost all months of the year, except for April, May, and December. Here, the geographic and seasonal distribution of P. plagiata are extended based on records from iNaturalist, a citizen science social network, and deposited material from scientific collections. In total, new records for 125 first-level administrative divisions in the Neotropical region were reported. The adult morphology and identification are discussed. Additionally, information on feeding habits and reproductive behavior are provided for the first time.

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Multimodal landscape of atherosclerotic plaques: A spatial omics approach with mass spectrometry imaging - Robin Joshi; Soon Yew Tang; Ujjalkumar Subhash Das; Daniel J. Boehmler; Antonijo Mrčela; Ronan Lordan; E. James Petersson; Aalim M. Weljie; Garret A. FitzGerald (Analytica Chimica Acta, 2025)

Cross‐Continental Analysis Shows That Disturbance Effects on Reptile Body Condition Do Not Predict Abundance Responses - Kristina J. Macdonald; Don A. Driscoll; Michael D. Craig; Robert A. Davis; Steven J. Hromada; C. M. Gienger; Lee A. Fitzgerald; Daniel J. Leavitt; Danielle K. Walkup; Rickard Abom; Adrian F. Wayne; Gordon R. Friend; et al. (Global Change Biology, 2025)
Ecological disturbances are discrete events that alter or transform the physical, chemical, or biological characteristics of ecosystems. Disturbance can cause animal populations to decline and, according to the risk‐disturbance hypothesis and population collapse framework, these declines can be predicted by declines in animal body condition. However, no research has empirically examined the general relationship between body condition and abundance, nor their relationship in response to disturbance. We used a combined dataset representing 33 studies and > 42,000 observations of 75 species from Australia, New Zealand, Spain and the United States of America to test predictions relating to the relationship between reptile body condition and abundance. We first investigated the relationship at the site level and then used meta‐analytical models to test whether populations showed linked changes in abundance and body condition in response to disturbance. We further tested whether key environmental and species traits influenced this relationship and whether there was a time‐lagged effect of body condition responses on abundance. We found a positive relationship between mean reptile body condition and abundance at the site level. However, the relationship was largely lost when investigating population responses to disturbance. As such, our results provided no support for the risk‐disturbance hypothesis and limited support for the population collapse framework. Therefore, the impacts of disturbance on reptile body condition cannot be assumed to reflect or predict abundance responses. We provide a new conceptual framework that shows how disturbances can modify or uncouple the relationship between abundance and body condition by influencing underlying drivers, such as predation, competition and resource availability. Monitoring programs that infer population impacts based on changes in body condition should first confirm the relationship between these two variables in the relevant study system.

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Comparative analysis of phenolic extracts obtained from Lippia alba (Mill.) N. E. Brown leaves by microwave-assisted extraction using eco-friendly solvents - Raphael Amancio de Jesus; Julio Manoel Andrade de Oliveira; José Michael da Silva; Mariana Oliveira Fraga; Wenes Ramos da Silva; Alberto Wisniewski Jr; José Carlos Freitas de Sá Filho; Arie Fitzgerald Blank; Daniel Alves de Souza; Elma Regina Silva de Andrade Wartha; Paulo Cesar de Lima Nogueira; Valéria Regina de Souza Moraes (Food Chemistry, 2025)

Multi‐trait responses in two marine diatoms to pH and irradiance reveal interactive effect of light and acidification, mediated by silicification - Billy FitzGerald‐Lowry; Daniel Aagren Nielsen; Rebecca Julianne Duncan; Alyson May Theseira; Georgia Thompson; Katherina Petrou (Limnology and Oceanography, 2025)
Ocean ecosystem shifts in response to anthropogenic climate change are impacting marine organisms, including phytoplankton. Ocean acidification and warming represent two key threats to marine phytoplankton, causing significant changes to the upper mixed layer of the ocean, reshuffling their distribution, and reorganizing their physiology and metabolism. In this study, we investigated changes in biomolecular composition and silicification rates of the two “model” diatom species Phaeodactylum tricornutum and Thalassiosira weissflogii under low (~ 350) and projected future (~ 800) p CO 2 concentrations with low (20 μ mol photons m −2 s −1 ) and high (200 μ mol photons m −2 s −1 ) light, simulating expected climate change‐induced impacts of ocean shoaling and acidification. Specifically, our study conditions elicited changes in lipid and protein content in both species. We also found a negative effect of p CO 2 on silica production under high light in T. weissflogii that was linked to improved photochemical efficiency. This interactive effect between light and p CO 2 with silica production suggests a potential controlling role of the frustule in diatom photosynthesis and photoprotection (energy balance). Based on these data, ocean shoaling and acidification have the potential to influence the nutritional value and biogeochemical role of diatoms through its effect on diatom frustule synthesis and photobiology.

Associations between MASLD, atrial fibrillation, cardiovascular events, mortality and aspirin use in older adults - Daniel Clayton-Chubb; Stuart K. Roberts; Ammar Majeed; Robyn L. Woods; Andrew M. Tonkin; Mark R. Nelson; Andrew T. Chan; Joanne Ryan; Cammie Tran; Alexander Hodge; John S. Lubel; Hans G. Schneider; et al. (GeroScience, 2024)

Comparative Description and Analysis of Oyster Aquaculture in Selected Atlantic Regions: Production, Market Dynamics, and Consumption Patterns - Johannes A. Iitembu; Daniel Fitzgerald; Themistoklis Altintzoglou; Pierre Boudry; Peter Britz; Carrie J. Byron; Daniel Delago; Sophie Girard; Colin Hannon; Marcia Kafensztok; Francisco Lagreze; Jefferson Francisco Alves Legat; et al. (Fishes, 2023)
In the face of an increasing world population and a subsequent need for an increase in sustainable and healthy food production, low trophic species, such as oysters, emerge as a promising alternative. However, regional variations in oyster production techniques, market dynamics, and consumption patterns create challenges for both the global and local industry’s growth. In this study, a descriptive qualitative analysis of oyster markets across seven Atlantic regions was carried out. The Pacific oyster (Crassostrea gigas) was found to be farmed in most Atlantic regions except the US but is classified as invasive in Sweden and potentially invasive in South Africa. Other farmed and/or harvested species include native species (C. gasar and C. rhizophorae) in Brazil, the American cupped oyster (C. virginica) in the US, and the European flat oyster (Ostrea edulis) in France, Sweden, and the US. In Irish farms, Pacific oysters are primarily for export to European markets. The marine aquaculture sectors of Sweden, South Africa, and Namibia, as well as Brazil’s farming for C. gasar, were found to be underdeveloped. This study also observed a variation in licensing, property rights, and regulatory frameworks. Financial challenges for small businesses, ecological implications of seed production techniques, biosecurity risks, and public health considerations are emphasized as critical areas for attention. This study offers valuable insights into the selected markets and can serve as a useful resource for policymakers, aquaculture practitioners, and stakeholders in optimizing global shellfish industry strategies.

Geographic and taxonomic variation in adaptive capacity among mountain-dwelling small mammals: Implications for conservation status and actions - Erik A. Beever; Jennifer L. Wilkening; Peter D. Billman; Lindsey L. Thurman; Kristina A. Ernest; David H. Wright; Alisha M. Gill; April C. Craighead; Nolan A. Helmstetter; Leona K. Svancara; Meghan J. Camp; Sabuj Bhattacharyya; et al. (Biological Conservation, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Biological studies and chromatograms aided by chemometric analysis in evaluation of seasonality and extraction method of Croton grewioides extracts - Vilma Menezes de Jesus Prado; Raphael Amancio de Jesus; Julio Manoel Andrade Oliveira; Arie Fitzgerald Blank; Daniel Pereira Bezerra; Milena Botelho Pereira Soares; Valdenizia Rodrigues Silva; Luciano de Souza Santos; Carmen Lúcia Cardoso; Adriana Ferreira Lopes Vilela; Paulo Cesar de Lima Nogueira; Valéria Regina de Souza Moraes (Brazilian Journal of Botany, 2022)

Using expert knowledge to support Endangered Species Act decision‐making for data‐deficient species - Daniel B. Fitzgerald; David R. Smith; David C. Culver; Daniel Feller; Daniel W. Fong; Jeff Hajenga; Matthew L. Niemiller; Daniel C. Nolfi; Wil D. Orndorff; Barbara Douglas; Kelly O. Maloney; John A. Young (Conservation Biology, 2021)
Many questions relevant to conservation decision‐making are characterized by extreme uncertainty due to lack of empirical data and complexity of the underlying ecologic processes, leading to a rapid increase in the use of structured protocols to elicit expert knowledge. Published ecologic applications often employ a modified Delphi method, where experts provide judgments anonymously and mathematical aggregation techniques are used to combine judgments. The Sheffield elicitation framework (SHELF) differs in its behavioral approach to synthesizing individual judgments into a fully specified probability distribution for an unknown quantity. We used the SHELF protocol remotely to assess extinction risk of three subterranean aquatic species that are being considered for listing under the U.S. Endangered Species Act. We provided experts an empirical threat assessment for each known locality over a video conference and recorded judgments on the probability of population persistence over four generations with online submission forms and R‐shiny apps available through the SHELF package. Despite large uncertainty for all populations, there were key differences between species’ risk of extirpation based on spatial variation in dominant threats, local land use and management practices, and species’ microhabitat. The resulting probability distributions provided decision makers with a full picture of uncertainty that was consistent with the probabilistic nature of risk assessments. Discussion among experts during SHELF's behavioral aggregation stage clearly documented dominant threats (e.g., development, timber harvest, animal agriculture, and cave visitation) and their interactions with local cave geology and species’ habitat. Our virtual implementation of the SHELF protocol demonstrated the flexibility of the approach for conservation applications operating on budgets and time lines that can limit in‐person meetings of geographically dispersed experts.

Refining the activity level-predation risk paradigm in larval anuran communities - Daniel Saenz; Kristen A. Baum; Lee A. Fitzgerald; Christopher M. Schalk (Aquatic Sciences, 2021)

A comparison of gait stability between younger and older adults while head turning - Caitlin Fitzgerald; Daniel Thomson; Adem Zebib; Peter J. Clothier; Amitabh Gupta (Experimental Brain Research, 2020)

Impacts of Urbanization and Development on Estuarine Ecosystems and Water Quality - Lauren A. Freeman; D. Reide Corbett; Allison M. Fitzgerald; Daniel A. Lemley; Antonietta Quigg; Cecily N. Steppe (Estuaries and Coasts, 2019)

Trophic niche segregation among herbivorous serrasalmids from rapids of the lower Xingu River, Brazilian Amazon - Marcelo C. Andrade; Daniel B. Fitzgerald; Kirk O. Winemiller; Priscilla S. Barbosa; Tommaso Giarrizzo (Hydrobiologia, 2019)

Migratory birds as vehicles for parasite dispersal? Infection by avian haemosporidians over the year and throughout the range of a long‐distance migrant - Paulo C. Pulgarín‐R; Camila Gómez; Nicholas J. Bayly; Staffan Bensch; Alyssa M. FitzGerald; Naima Starkloff; Jeremy J. Kirchman; Ana M. González‐Prieto; Keith A. Hobson; Judit Ungvari‐Martin; Heather Skeen; María Isabel Castaño; et al. (Journal of Biogeography, 2019)
Aim The role of migratory birds in the spread of parasites is poorly known, in part because migratory strategies and behaviours potentially affecting transmission are not easy to study. We investigated the dynamics of infection by blood parasites through the annual cycle of a long‐distance Nearctic–Neotropical migratory songbird to examine the role of this species in dispersing parasites between continents. Location The Americas. Taxon Grey‐cheeked Thrush ( Catharus minimus , Aves, Passeriformes, Turdidae), Birds. Methods We used molecular and microscopy screening of haemosporidian parasites ( Plasmodium , Haemoproteus , and Leucocytozoon ) to examine the prevalence, distribution, and diversity of lineages through the annual cycle (breeding, migration, and wintering) of the grey‐cheeked thrush in North and Central America, Santa Marta mountains, the Andes, and the Amazon. We aimed to identify transmission areas, to examine the degree of sharing of haemosporidian lineages with resident birds in various areas and to assess the potential role of immunologically naïve juvenile individuals in parasite transmission. Results Prevalence and lineage diversity of haemosporidians varied significantly over time, being higher during breeding and fall and spring migration, and declining during wintering. Grey‐cheeked thrush shared few parasite lineages with tropical resident birds and slightly more lineages with other migratory and resident boreal species. We detected gametocytes in blood during spring migration stopover, but these were of lineages not found in resident tropical birds, indicating relapses of parasites transmitted elsewhere. Transmission likely occurs mostly on the breeding grounds, where juveniles and adults carried lineages restricted to closely related species of thrushes and other species of boreal birds. Main conclusions Long‐distance migratory songbirds are likely not important dispersers of blood parasites because there are ecological and evolutionary barriers to the interchange of parasites across vastly separated areas. Further work with thorough spatial and temporal sampling across other species, and considering the role of vectors, is necessary to understand the ecological and evolutionary factors explaining the distribution of parasites over broad scales.

Climate change impact and adaptation for wheat protein - Senthold Asseng; Pierre Martre; Andrea Maiorano; Reimund P. Rötter; Garry J. O’Leary; Glenn J. Fitzgerald; Christine Girousse; Rosella Motzo; Francesco Giunta; M. Ali Babar; Matthew P. Reynolds; Ahmed M. S. Kheir; et al. (Global Change Biology, 2019)
Wheat grain protein concentration is an important determinant of wheat quality for human nutrition that is often overlooked in efforts to improve crop production. We tested and applied a 32‐multi‐model ensemble to simulate global wheat yield and quality in a changing climate. Potential benefits of elevated atmospheric CO 2 concentration by 2050 on global wheat grain and protein yield are likely to be negated by impacts from rising temperature and changes in rainfall, but with considerable disparities between regions. Grain and protein yields are expected to be lower and more variable in most low‐rainfall regions, with nitrogen availability limiting growth stimulus from elevated CO 2 . Introducing genotypes adapted to warmer temperatures (and also considering changes in CO 2 and rainfall) could boost global wheat yield by 7% and protein yield by 2%, but grain protein concentration would be reduced by −1.1 percentage points, representing a relative change of −8.6%. Climate change adaptations that benefit grain yield are not always positive for grain quality, putting additional pressure on global wheat production.

Multimodel ensembles improve predictions of crop–environment–management interactions - Daniel Wallach; Pierre Martre; Bing Liu; Senthold Asseng; Frank Ewert; Peter J. Thorburn; Martin van Ittersum; Pramod K. Aggarwal; Mukhtar Ahmed; Bruno Basso; Christian Biernath; Davide Cammarano; et al. (Global Change Biology, 2018)
A recent innovation in assessment of climate change impact on agricultural production has been to use crop multimodel ensembles ( MME s). These studies usually find large variability between individual models but that the ensemble mean (e‐mean) and median (e‐median) often seem to predict quite well. However, few studies have specifically been concerned with the predictive quality of those ensemble predictors. We ask what is the predictive quality of e‐mean and e‐median, and how does that depend on the ensemble characteristics. Our empirical results are based on five MME studies applied to wheat, using different data sets but the same 25 crop models. We show that the ensemble predictors have quite high skill and are better than most and sometimes all individual models for most groups of environments and most response variables. Mean squared error of e‐mean decreases monotonically with the size of the ensemble if models are added at random, but has a minimum at usually 2–6 models if best‐fit models are added first. Our theoretical results describe the ensemble using four parameters: average bias, model effect variance, environment effect variance, and interaction variance. We show analytically that mean squared error of prediction ( MSEP ) of e‐mean will always be smaller than MSEP averaged over models and will be less than MSEP of the best model if squared bias is less than the interaction variance. If models are added to the ensemble at random, MSEP of e‐mean will decrease as the inverse of ensemble size, with a minimum equal to squared bias plus interaction variance. This minimum value is not necessarily small, and so it is important to evaluate the predictive quality of e‐mean for each target population of environments. These results provide new information on the advantages of ensemble predictors, but also show their limitations.

We need better understanding about functional diversity and vulnerability of tropical freshwater fishes - Jean R. S. Vitule; Angelo A. Agostinho; Valter M. Azevedo-Santos; Vanessa S. Daga; William R. T. Darwall; Daniel B. Fitzgerald; Fabrício A. Frehse; David J. Hoeinghaus; Dilermando P. Lima-Junior; André L. B. Magalhães; Mário L. Orsi; André A. Padial; et al. (Biodiversity and Conservation, 2017)

Seasonal changes in the assembly mechanisms structuring tropical fish communities - Daniel B. Fitzgerald; Kirk O. Winemiller; Mark H. Sabaj Pérez; Leandro M. Sousa (Ecology, 2017)
Despite growing interest in trait‐based approaches to community assembly, little attention has been given to seasonal variation in trait distribution patterns. Mobile animals can rapidly mediate influences of environmental factors and species interactions through dispersal, suggesting that the relative importance of different assembly mechanisms can vary over short time scales. This study analyzes seasonal changes in functional trait distributions of tropical fishes in the Xingu River, a major tributary of the Amazon with large predictable temporal variation in hydrologic conditions and species density. Comparison of observed functional diversity revealed that species within wet‐season assemblages were more functionally similar than those in dry‐season assemblages. Further, species within wet‐season assemblages were more similar than random expectations based on null model predictions. Higher functional richness within dry season communities is consistent with increased niche complementarity during the period when fish densities are highest and biotic interactions should be stronger; however, null model tests suggest that stochastic factors or a combination of assembly mechanisms influence dry‐season assemblages. These results demonstrate that the relative influence of community assembly mechanisms can vary seasonally in response to changing abiotic conditions, and suggest that studies attempting to infer a single dominant mechanism from functional patterns may overlook important aspects of the assembly process. During the prolonged flood pulse of the wet season, expanded habitat and lower densities of aquatic organisms likely reduce the influence of competition and predation. This temporal shift in the influence of different assembly mechanisms, rather than any single mechanism, may play a large role in maintaining the structure and diversity of tropical rivers and perhaps other dynamic and biodiverse systems.

Morphologic and trophic diversity of fish assemblages in rapids of the Xingu River, a major Amazon tributary and region of endemism - Mario Alejandro Zuluaga-Gómez; Daniel B. Fitzgerald; Tommaso Giarrizzo; Kirk O. Winemiller (Environmental Biology of Fishes, 2016)

Genome-wide association of familial prostate cancer cases identifies evidence for a rare segregating haplotype at 8q24.21 - Craig C. Teerlink; Daniel Leongamornlert; Tokhir Dadaev; Alun Thomas; James Farnham; Robert A. Stephenson; Shaun Riska; Shannon K. McDonnell; Daniel J. Schaid; William J. Catalona; S. Lilly Zheng; Kathleen A. Cooney; et al. (Human Genetics, 2016)

From richer to poorer: successful invasion by freshwater fishes depends on species richness of donor and recipient basins - Daniel B. Fitzgerald; Michael Tobler; Kirk O. Winemiller (Global Change Biology, 2016)
Evidence for the theory of biotic resistance is equivocal, with experiments often finding a negative relationship between invasion success and native species richness, and large‐scale comparative studies finding a positive relationship. Biotic resistance derives from local species interactions, yet global and regional studies often analyze data at coarse spatial grains. In addition, differences in competitive environments across regions may confound tests of biotic resistance based solely on native species richness of the invaded community. Using global and regional data sets for fishes in river and stream reaches, we ask two questions: (1) does a negative relationship exist between native and non‐native species richness and (2) do non‐native species originate from higher diversity systems. A negative relationship between native and non‐native species richness in local assemblages was found at the global scale, while regional patterns revealed the opposite trend. At both spatial scales, however, nearly all non‐native species originated from river basins with higher native species richness than the basin of the invaded community. Together, these findings imply that coevolved ecological interactions in species‐rich systems inhibit establishment of generalist non‐native species from less diverse communities. Consideration of both the ecological and evolutionary aspects of community assembly is critical to understanding invasion patterns. Distinct evolutionary histories in different regions strongly influence invasion of intact communities that are relatively unimpacted by human actions, and may explain the conflicting relationship between native and non‐native species richness found at different spatial scales.

Functional traits, convergent evolution, and periodic tables of niches - Kirk O. Winemiller; Daniel B. Fitzgerald; Luke M. Bower; Eric R. Pianka (Ecology Letters, 2015)
Ecology is often said to lack general theories sufficiently predictive for applications. Here, we examine the concept of a periodic table of niches and feasibility of niche classification schemes from functional trait and performance data. Niche differences and their influence on ecological patterns and processes could be revealed effectively by first performing data reduction/ordination analyses separately on matrices of trait and performance data compiled according to logical associations with five basic niche ‘dimensions’, or aspects: habitat, life history, trophic, defence and metabolic. Resultant patterns then are integrated to produce interpretable niche gradients, ordinations and classifications. Degree of scheme periodicity would depend on degrees of niche conservatism and convergence causing species clustering across multiple niche dimensions. We analysed a sample data set containing trait and performance data to contrast two approaches for producing niche schemes: species ordination within niche gradient space, and niche categorisation according to trait‐value thresholds. Creation of niche schemes useful for advancing ecological knowledge and its applications will depend on research that produces functional trait and performance datasets directly related to niche dimensions along with criteria for data standardisation and quality. As larger databases are compiled, opportunities will emerge to explore new methods for data reduction, ordination and classification.

Associations of prostate cancer risk variants with disease aggressiveness: results of the NCI-SPORE Genetics Working Group analysis of 18,343 cases - Brian T. Helfand; Kimberly A. Roehl; Phillip R. Cooper; Barry B. McGuire; Liesel M. Fitzgerald; Geraldine Cancel-Tassin; Jean-Nicolas Cornu; Scott Bauer; Erin L. Van Blarigan; Xin Chen; David Duggan; Elaine A. Ostrander; et al. (Human Genetics, 2015)

Quantifying the effects of light intensity on bioproduction and maintenance energy during photosynthetic growth of Rhodobacter sphaeroides - Saheed Imam; Colin M. Fitzgerald; Emily M. Cook; Timothy J. Donohue; Daniel R. Noguera (Photosynthesis Research, 2015)

Effects of oxycodone on brain responses to emotional images - Margaret C. Wardle; Daniel A. Fitzgerald; Michael Angstadt; Christine A. Rabinak; Harriet de Wit; K. Luan Phan (Psychopharmacology, 2014)

Crack cocaine use impairs anterior cingulate and prefrontal cortex function in women with HIV infection - Vanessa J. Meyer; Deborah M. Little; Daniel A. Fitzgerald; Erin E. Sundermann; Leah H. Rubin; Eileen M. Martin; Kathleen M. Weber; Mardge H. Cohen; Pauline M. Maki (Journal of NeuroVirology, 2014)

Association analysis of 9,560 prostate cancer cases from the International Consortium of Prostate Cancer Genetics confirms the role of reported prostate cancer associated SNPs for familial disease - Craig C. Teerlink; Stephen N. Thibodeau; Shannon K. McDonnell; Daniel J. Schaid; Antje Rinckleb; Christiane Maier; Walther Vogel; Geraldine Cancel-Tassin; Christophe Egrot; Olivier Cussenot; William D. Foulkes; Graham G. Giles; et al. (Human Genetics, 2014)

Alcohol attenuates amygdala–frontal connectivity during processing social signals in heavy social drinkers - Stephanie M. Gorka; Daniel A. Fitzgerald; Andrea C. King; K. Luan Phan (Psychopharmacology, 2013)

Validation of prostate cancer risk-related loci identified from genome-wide association studies using family-based association analysis: evidence from the International Consortium for Prostate Cancer Genetics (ICPCG) - Guangfu Jin; Lingyi Lu; Kathleen A. Cooney; Anna M. Ray; Kimberly A. Zuhlke; Ethan M. Lange; Lisa A. Cannon-Albright; Nicola J. Camp; Craig C. Teerlink; Liesel M. FitzGerald; Janet L. Stanford; Kathleen E. Wiley; et al. (Human Genetics, 2012)

ERP correlates of response inhibition after-effects in the stop signal task - Daniel J. Upton; Peter G. Enticott; Rodney J. Croft; Nicholas R. Cooper; Paul B. Fitzgerald (Experimental Brain Research, 2010)

Reactive glia are recruited by highly proliferative brain metastases of breast cancer and promote tumor cell colonization - Daniel P. Fitzgerald; Diane Palmieri; Emily Hua; Elizabeth Hargrave; Jeanne M. Herring; Yongzhen Qian; Eleazar Vega-Valle; Robert J. Weil; Andreas M. Stark; Alexander O. Vortmeyer; Patricia S. Steeg (Clinical & Experimental Metastasis, 2008)

s of papers presented at the 81st annual meeting of The Potato Association of America Charlottetown, P.E.I., Canada August 3 – 7, 1997 - S. T. Ali-Khan; C. Hetner; L. Ladislav; V. Currie; Walter J. Arsenault; A. Naseer Aziz; Janet E. A. Seabrook; George C. C. Tai; J. B. Bamberg; Alfonso H. del Rio; Max Martin; J. B. Bamberg; et al. (American Journal of Potato Research, 1997)